Transcatheter mitral valve repair with MitraClip® enabling single lung transplantation: A case report - François M. Carlier; Michel Dumonceaux; Thomas Planté-Bordeneuve; Patrick Evrard; Eric Marchand; Asmae Belhaj; Benoît Rondelet; Fabian Demeure (Heliyon)
Post-capillary hypertension resulting from mitral regurgitation is typically considered a contraindication for single lung transplantation due to heightened risks of primary graft dysfunction. This case report highlights a 66-year-old COPD patient with severe mitral regurgitation who was deemed ineligible for surgical mitral replacement. As an alternative, transcatheter mitral valve replacement was successfully performed, resulting in the normalization of pulmonary artery pressures. Consequently, the patient became eligible for single lung transplantation, which was conducted successfully in the subsequent months. Eighteen months post-lung transplantation, the patient now experiences a normal functional status and excellent lung function. In conclusion, transcatheter mitral valve replacement appears to be a safe alternative to surgery for normalizing post-capillary pulmonary hypertension in patients with chronic respiratory diseases. This approach could potentially facilitate lung transplantation (LTx) in eligible candidates.